(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study was conducted to measure the satisfaction level of customers who previously experienced the services and facilities of Cariño Resort. The researchers developed this study to determine the impact of customer satisfaction on management strategies and decisions. It also seeks to identify what services and facilities of Cariño Resort need to be improved by management to maintain/increase the customer’s current expectations. This study used a descriptive research method to collect and analyse data to understand concepts, opinions, and experiences. This study utilised a purposive sampling technique that was selected based on the characteristics of a population and distributed to 50 customers of Cariño Resort. Based on the survey result, most customers that visited the resort are aged 15-30, which got 94%, while those aged 31-50 got 6%. 50% of customers were females, while 48% were males. The majority of customers aged 15-30 are employed (29). Most employed are minimum wage earners (18); the rest (7) are below the minimum, while four earn above minimum wage. The customers assessed the following variables in terms of service quality: behaviour of the staff, dissemination of relevant information, and prompt response to customer requirements and demand. Regarding facilities handling and maintenance, the following were evaluated: maintenance of sufficient lighting in access areas, ensuring the cleanliness of the rooms and pools, provision of safety and security staff and facilities, and regular repair and maintenance of defective facilities. Overall, the customers rated the resort’s performance as “satisfied.” To respond to the customer’s requirements and demands, Cariño Resort management adopted the following strategies. On services: provides immediate action on issues/problems encountered by the customer; sets up a monitoring system to determine the service lapses; and formulates strategies to address identified lapses. The researcher recommended the following to increase customer satisfaction: set up a monitoring system to document the customer’s concerns; conduct regular training for the employees to enhance their capability, and conduct regular evaluations regarding the strategies and performances of the resort to provide high-quality service continuously; maintain customer service etiquette, and maintain transparency; use different social media platforms, leverage free Wi-Fi, establish a feedback system by using the social media marketing system, value the customer feedback, and empower their team to delight customers to enhance the customer experience which will lead to improved customer satisfaction.